The Effectiveness of the Quantum and Discovery Learning Models on Learning Achievement of Islamic Education in Junior High Schools - Ifa Lidia Wati; Rihab Wit Daryono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Low student learning outcomes in Islamic religious education lessons so that the required learning competencies are not achieved. This research aims to improve students' cognitive learning outcomes through QL and DL learning models. Method: The research used in this research is experimental research with the type of research used as Quasi Experiment using a non-random pretest-posttest control group design. Pretest-Posttest Non-Equivalent Control Group Design. The data collection technique used in this research was pretest and posttest in experimental classes 7A and 7B. Results: The results of this study show that the QL and DL methods can improve students' cognitive abilities with learning outcomes for experimental class 7A (QL) while for experimental class 7B (Discovery Learning). Meanwhile, the Independent Sample T-test results show significant differences in learning outcomes between experimental class 7A (QL) and experimental class 7B (Discovery Learning) with Sig. (2-tailed) smaller than 0.05. So, the QL learning model is more effectively used to improve students' cognitive learning outcomes than the DL learning model. Novelty: The application of QL in this research and the Discovery of Learning to improve student outcomes can be explored in particular educational contexts, such as STEM, arts, or foreign language learning. Both models can be adapted or modified to achieve optimal learning outcomes.